2017
DOI: 10.4067/s0718-95162017005000032
|View full text |Cite
|
Sign up to set email alerts
|

Boron toxicity effects on grafted and non-grafted pepper (Capsicum annuum) plants

Abstract: Grafting is a vegetative plant propagation technique. In a grafted plant, the upward supply of water and mineral nutrients as well as the downward flow of photosynthesis are modified. In this context, the objectives of this work were to find out whether the grafting of pepper plants (Capsicum annuum L. family Solanaceae) reduces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…MEL effectively improved proline level, metabolite content, antioxidant enzymes, and their gene expression levels in Brassica napus under Se toxicity (Ulhassan et al, 2019). In another study, MEL treatment considerably enhanced net photosynthetic rate, growth traits, leaf gas exchange elements, and maintained macro-and micro-nutrient content in pepper leaves under B toxicity (Sarafi et al, 2017). MEL application improved antioxidant enzyme activities and root growth and reduced the MDA and proline levels in the roots of melon seedlings under Cu toxicity (Hu et al, 2020).…”
Section: Heavy Metalsmentioning
confidence: 93%
See 1 more Smart Citation
“…MEL effectively improved proline level, metabolite content, antioxidant enzymes, and their gene expression levels in Brassica napus under Se toxicity (Ulhassan et al, 2019). In another study, MEL treatment considerably enhanced net photosynthetic rate, growth traits, leaf gas exchange elements, and maintained macro-and micro-nutrient content in pepper leaves under B toxicity (Sarafi et al, 2017). MEL application improved antioxidant enzyme activities and root growth and reduced the MDA and proline levels in the roots of melon seedlings under Cu toxicity (Hu et al, 2020).…”
Section: Heavy Metalsmentioning
confidence: 93%
“…In addition, MEL further enhanced the antioxidant enzyme system, along with a decline in the ROS level in spinach seedlings (Moussa and Algamal, 2017). MEL positively regulates the growth of tobacco under lead stress (Kobylińska et al, 2017), radish under Cd toxicity (Xu et al, 2020), and pepper under boron stress (Sarafi et al, 2017). Table 5 provides an overview of the protective functions of MEL in horticultural crops under heavy metal toxicity.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…Alamri et al (2018) indicated effects of soil boron concentrations on germination and seedling growth parameters and reported that low boron concentrations (0.5 mg L -1 ) had positive effects on germination and seedling growth parameters, but high concentrations (1.0 mg L -1 ) reduced germination rates and seedling growth parameters significantly. In pepper plants, boron toxicity symptoms (slight chlorosis along the leaf edges) were encountered when the boron concentration of nutrient solution increased to 5.0 mg L -1 (Sarafi et al, 2017). Decreasing germiantion ratios and germination index values of pepper plants were reported at boron concentrations of over 2.0 mg L -1 (Turhan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pepper (Capsicum annuum L.) is a valuable crop not only because of its economic significance but also of the nutritional value of its fruits, which are a major source of antioxidants (Sarafi et al, 2017) and minerals. A proportion greater than 25% of the worlds' population consumes peppers every day (d) (Namiki, 1990).…”
Section: Introductionmentioning
confidence: 99%